Development of videoscribe-based learning media for biodiversity material with the environmental potential of Rahmat Zoo and Park - Annisa Aulia Nanda; Syarifah Widya Ulfa (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Biodiversity is often considered a complex topic for students to understand. Therefore, media connecting the material with the environment's potential is needed. With the development of technology, interactive learning media such as videoscribe is one solution. Videoscribe is a video media that uses the concept of a blackboard, where virtual hands appear to draw or write on the screen. This research aims to develop videoscribe media that is valid, practical, and effective. Researchers used the Research and Development (R&D) method with the Borg & Gall model consisting of seven stages: identification of potential problems, data collection, product design, design validation, design revision, product trial, and final revision. The research instruments included interviews with teachers, student needs questionnaires, media and material expert validation sheets, and teacher and student response questionnaires. To measure the effectiveness of the media, 10 multiple choice questions were used. The results showed that the validity of videoscribe according to media experts reached 97.5%, and according to material experts 100%, both in the very valid category. This media is also considered very practical, with 97.72% teacher response and 92.86% student response. The effectiveness of the media was measured using N-Gain from the pretest and posttest results, which showed a score of 0.76, including in the effective category. The videoscribe media developed is considered valid, practical, and effective for use in the learning process.Abstrak. Keanekaragaman hayati sering dianggap sebagai topik yang sulit dipahami oleh siswa. Oleh karena itu, dibutuhkan media yang dapat menghubungkan materi dengan potensi lingkungan. Dengan perkembangan teknologi, media pembelajaran interaktif seperti videoscribe menjadi salah satu solusi. Videoscribe adalah media video yang menggunakan konsep papan tulis, di mana tangan virtual tampak menggambar atau menulis di layar. Penelitian ini bertujuan untuk mengembangkan media videoscribe yang valid, praktis, dan efektif. Peneliti menggunakan metode Research and Development (R&D) dengan model Borg & Gall yang terdiri dari tujuh tahap, yaitu identifikasi potensi dan masalah, pengumpulan data, desain produk, validasi desain, revisi desain, uji coba produk, dan revisi akhir. Instrumen penelitian meliputi wawancara dengan guru, kuesioner kebutuhan siswa, lembar validasi ahli media dan materi, serta angket respon guru dan siswa. Untuk mengukur keefektifan media, digunakan 10 soal pilihan ganda. Hasil penelitian menunjukkan bahwa validitas videoscribe menurut ahli media mencapai 97,5%, dan menurut ahli materi 100%, keduanya dalam kategori sangat valid. Media ini juga dinilai sangat praktis, dengan respon guru 97,72% dan respon siswa 92,86%. Keefektifan media diukur menggunakan N-Gain dari hasil pretest dan posttest, yang menunjukkan skor 0,76, termasuk dalam kategori efektif. Jadi, media videoscribe yang dikembangkan ini dinilai valid, praktis, dan efektif untuk digunakan dalam proses pembelajaran.